Subtypes of muscarinic receptors in rat duodenum - A comparison with rabbit vas deferens, rat atria, guinea-pig ileum and gallbladder by using imperialine - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1999)
The specific binding of [H-3]QNB to rat duodenum smooth muscle membranes was a saturable process and Scatchard transformation of the saturation curves indicated a linear plot (n(H) = 1.017 +/- 0.071). The K-D and B-max values were 0.168 +/- 0.025 nM and 46.7 +/- 8.6 fmol/mg protein, respectively. Analyses of competition curves using pirenzepine and guanylpirenzepine indicated more than one class of binding site. A minor population of muscarinic binding sites showed high affinity (M-1) for both pirenzepine (19.3 +/- 1.2%; pK(i) = 8.29 +/- 0.36) and guanylpirenzepine (29.4 +/- 2.0%; pK(i) = 7.28 +/- 0.11). The antagonistic affinity values of pirenzepine and guanylpirenzepine for the remaining low affinity binding sites, and that of methoctramine indicated the presence of both M-2 and M-3 subtypes. McN-A-343 produced relaxations in rat duodenum and inhibited twitch contractions of rabbit vas deferens induced by electrical stimulation in a concentration dependent manner. Carbachol (Cch) exerted concentration-dependent negative inotropic effect in rat atria and contractile effects in guinea-pig gallbladder and ileum longitudinal muscle-myenteric plexus preparation. Imperaline displaced the concentration-response curves to McN-A-343 and Cch to the right in parallel, without affecting the maximum responses in all tissues studied. The rank order of the pA(2) values was rabbit vas deferens > rat atria > guinea-pig gallbladder = guinea-pig ileum > rat duodenum. The presynaptic muscarinic receptors at the rat duodenum and rabbit vas deferens were concluded to be of M-1 and M-2 subtypes, respectively. (C) 1999 Elsevier Science Inc. All rights reserved.
Keywords: rat duodenum; muscarinic; imperialine; methoctramine; pirenzepine; guanylpirenzepine; SMOOTH-MUSCLE MEMBRANES; BINDING CHARACTERISTICS; 4-DAMP ANALOGS; HETEROGENEITY; ANTAGONIST; M2; M1; M1-RECEPTOR; M2-RECEPTOR; INHIBITION